The controls of the Human Organs Removal and Transplantation Under the Algerian Health Code - Rouahna, Nadia (Journal of Human Sciences, 2025)
The world has achieved a significant progress in medicine, due to the enormous scientific discoveries , so that enable to save many patients’ lives , and rid them of their pains ; notably after the success of the organ removal and transplantation . and it was incumbent to annex this progress with some updated legal provisions, to frame and control this process, so as not depart from its framework and noble purposes, and even be reconcile between the interests of the donor’s in maintaining the safety and dignity of his body , and the recipient patient in benefiting and utilizing the donated organ, And that’s what the Algerian legislator tried to embody in the Algerian Health Law N° 18 -11.